Mindware : tools for smart thinking - Nisbett, Richard E. (New York : Farrar, Straus and Giroux, 2015)
A psychology expert offers a tool kit for thinking more clearly and making better decisions, explaining how to reframe problems using simplified concepts from science and statistics, including the law of large numbers, statistical regression, cost-benefit analysis, and causation and correlation.
Scientific and philosophical concepts can change the way we solve problems by helping us to think more effectively about our behavior and our world. Surprisingly, despite their utility, many of these tools remain unknown to most of us. In Mindware, psychologist Richart E. Nisbett presents these ideas in clear and accessible detail. Nisbett has made a career of studying and teaching such powerful problem-solving concepts as the law of large numbers, statistical regression, cost-benefit analysis, sunk costs and opportunity costs, and causation and correlation, probing the best methods for teaching others how to use them effectively in their daily lives. In this book, Nisbett shows how to frame common problems in such a way that these scientific and staitistical principles can be applied to them. The result is a practical guide to the most essential tools of reasoning ever developed--tools that can easily be used to make better professional, business, and personal decisions.--From publisher description.
pt. 1. Thinking about thought -- Everything's an inference -- The power of the situation -- The rational unconscious -- pt. 2. The formerly dismal science -- Should you think like an economist? -- Spilt milk and free lunch -- Foiling foibles -- pt. 3. Coding, counting, correlation, and causality -- Odds and Ns -- Linked up -- pt. 4. Experiments -- Ignore the HiPPO -- Experiments natural and experiments proper -- Eekonomics -- Don't ask, can't tell -- pt. 5. Thinking, straight and curved -- Logic -- Dialectical reasoning -- pt. 6. Knowing the world -- KISS and tell -- Keeping it real -- Conclusion: The tools of the lay scientist.
Includes bibliographical references (pages 293-305) and index.
Keywords: Reasoning; Thought and thinking; Decision Making; Thinking; Reasoning; Thought and thinking; Denken; Entscheidung